Seal Hunters of the Archipelago: Kirkkokangas IV settlement site of Kiukainen Culture in Pori, Satakunta - Väisänen, Teemu; Soisalo, Janne (Suomen arkeologinen seura ry, 2026)
This article presents the results of archaeological research at the Kirkkokangas IV settlement site in Pori, Satakunta, Finland, dated to the Kiukainen culture (ca. 2500–1750 BC). The study combines evidence from surface survey and a trial excavation conducted in 1996 and 1999 with systematic excavations carried out in 2021–2023. The results reveal a well-preserved coastal site specialised in seal hunting and fishing. The assemblage comprises lithic artefacts, Kiukainen Ware pottery, and osteological material dominated by seal remains. Radiocarbon dates place the main phase of occupation between 2000 and 1800 BC. Reconstruction of the palaeoenvironment indicates that the site was situated within a sheltered outer-archipelago setting during the Late Stone Age. The site’s environmental context, lithic technology, and faunal composition support its inter-pretation as a task-specific hunting station linked to larger settlement centres in the Kokemäenjoki River delta. Comparative analysis with contemporaneous Kiukainen culture sites, including Etukämppä and Kraakanmäki, highlights the role of specialised maritime sites within broader subsistence and settlement strate-gies during the Late Neolithic – Early Metal Period transition in western Finland.